Supporting International Students' English Language Communication Skills Development: What works, what doesn't and what might - Briguglio, Carmela; Anyanwu, Regina (Promaco Conventions, 2001)
The Curtin Business School (CBS) Communication Skills Centre was established for the purpose of providing support to its student population, both local and international, and also to assist staff to be better equipped to deal with student needs. Now in its third year of operation, the Centre has provided student and staff support in a variety of ways and using different strategies. This paper examines some of the strategies developed by Centre staff and describes those that have been more successful. It also discusses some of the issues which remain in this area and examines some possible solutions.